Influence of interstitial elements on internal friction measurements in Nb and Nb-Zr alloys - Florencio, O.; deFreitas, W. A.; Botta, W. J.; Grandini, Carlos Roberto [UNESP]; Jordao, JAR (Editions Physique, 1996)
Internal friction and frequency measurements as a function of temperature have been carried out in Nb and Nb-Zr policrystalline samples, using a torsion pendulum in the temperature range between 300K and 700K the heating rate was 1K/min and the pressure was kept better than 5x10(-3) mbar. Metals with bce lattice containing solute atoms dissolved interstitially often show anelastic behaviour due to a process know as stress-induced ordering responsible for the appearance of Snoek peaks. In the Nb sample it has been identified two constituent peaks corresponding to the interstitial-matrix interactions (Nb-O and Nb-N), but for the Nb-Zr samples with interstitial solute concentrations very close to those measured for the unalloyed Nb, it was not observed any mechanical relaxation peaks due to the presence of oxygen and nitrogen in solid solution.